2013
DOI: 10.1155/2013/547670
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Hepatic Encephalopathy

Abstract: Minimal hepatic encephalopathy (MHE) is the earliest form of hepatic encephalopathy and can affect up to 80% of cirrhotic patients. By definition, it has no obvious clinical manifestation and is characterized by neurocognitive impairment in attention, vigilance and integrative function. Although often not considered to be clinically relevant and, therefore, not diagnosed or treated, MHE has been shown to affect daily functioning, quality of life, driving and overall mortality. The diagnosis of MHE has traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…Minimal HE, the earliest stage of HE, occurs in up to 80 % of cirrhotics. It manifests with significant impairment in attention, psychomotor speed, visuospatial perception, response inhibition, and delayed information processing [91,92]. The presence of HE, even at the subclinical level, complicates significantly the patient's quality of life and their medical management [91,93,94].…”
Section: Integrating Palliative Care With Esld Managementmentioning
confidence: 99%
“…Minimal HE, the earliest stage of HE, occurs in up to 80 % of cirrhotics. It manifests with significant impairment in attention, psychomotor speed, visuospatial perception, response inhibition, and delayed information processing [91,92]. The presence of HE, even at the subclinical level, complicates significantly the patient's quality of life and their medical management [91,93,94].…”
Section: Integrating Palliative Care With Esld Managementmentioning
confidence: 99%
“…1,2 The diagnosis of CHE requires sensitive neuropsychological cognitive testing. However, no agreement exists among experts about which standardized screening tools should be used to diagnose CHE.…”
Section: Introductionmentioning
confidence: 99%
“…4 Studies using a variety of such tests have concluded that the prevalence of CHE in cirrhotic patients ranges from 30% to 80%. 2 Numerous studies indicate that cirrhotic patients with CHE may have significantly reduced fitness to operate motor vehicles or safely perform in occupations requiring concentration, dexterity, and normal reaction times for safe performance. 2,5 Patients with OHE have demonstrable impairments of driving skills (discussed later).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of MHE is based on a battery of psychometric tests (Ciecko-Michalska et al 2012;Weissenborn 2013). The psychometric hepatic encephalopathy score (PHES) (Kircheis et al 2014) and Stroop smart phone application (Stinton and Jayakumar 2013) have been proposed to screen MHE. The diagnostic accuracy of psychometric tests is limited (Kircheis et al 2014).…”
Section: Introductionmentioning
confidence: 99%